Running government like a business: implications for public administration theory and practice - Box, Richard C. (1999)
The public sector faces increasing demands to run government like a business, importing private-sector concepts such as entrepreneurism, privatization, treating the citizen like a "customer," and management techniques derived from the production process. The idea that government should mimic the market is not new in American public administration, but the current situation is particularly intense. The new public management seeks to emphasize efficient, instrumental implementation of policies, removing substantive policy questions from the administraive realm. This revival of the politics-administration dichotomy threatens core public-sector values of citizen self-governance and the administrator as servant of the public interest. The article examines the political culture that encourages expansion of market-like practices in the American public sector, explores the issues of the purpose and scope of government and the role of the public-service practitioner, and offers a framework for the study and practice of public administration based on citizenship and public service. - Reproduced
Keywords: Public administration